Current trends in explosive detection techniques - Caygill, J. S.; Davis, Frank; Higson, Seamus P. J. (Elsevier Science B.V., Amsterdam., 2012)
The detection of explosives and explosive-related compounds has become a heightened priority in recent years for homeland security and counter-terrorism applications. There has been a huge increase in research within this area- through both the development of new, innovative detection approaches and the improvement of existing techniques. Developments for miniaturisation, portability, field-ruggedisation and improvements in stand-off distances, selectivity and sensitivity have been necessary to develop and improve techniques. This review provides a consolidation of information relating to recent advances in explosive detection techniques without being limited to one specific research area or explosive type. The focus of this review will be towards advances in the last 5 years, with the reader being referred to earlier reviews where appropriate.